Epitaxial growth of Mg2Si films on strontium titanate single crystals. Issue 12 (11th November 2013) - Akiyama, Kensuke; Katagiri, Atsuo; Ogawa, Shota; Matsushima, Masaaki; Funakubo, Hiroshi; Maeda, Yoshihito; Suzuki, Motofumi
Abstract (110)‐ and (111)‐oriented Mg2Si films were grown at 325 °C on (100) and (110), and (111) SrTiO3 substrates, respectively, by RF magnetron sputtering method. X‐ray pole figure measurement showed that (110)‐oriented Mg2Si films on (100) and (110) SrTiO3 substrates were in‐plane‐aligned epitaxially grown ones. (110)‐oriented epitaxial films on (100) SrTiO3 substrates consisted of two types of varians in‐plane rotating at an angle of 90°, while epitaxial films on (110) SrTiO3 substrates consisted of single type of domains. On the other hand, (111)‐oriented Mg2Si films on (111) SrTiO3 substrates were in‐plane‐random one‐axis oriented films. (© 2013 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)